2012
DOI: 10.1016/j.tics.2011.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale brain systems in ADHD: beyond the prefrontal–striatal model

Abstract: Attention-deficit/hyperactivity disorder (ADHD) has long been thought to reflect dysfunction of prefrontal-striatal circuitry, with involvement of other circuits largely ignored. Recent advances in systems neuroscience-based approaches to brain dysfunction enable the development of models of ADHD pathophysiology that encompass a number of different large-scale “resting state” networks. Here we review progress in delineating large-scale neural systems and illustrate their relevance to ADHD. We relate frontopari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

58
497
1
13

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 601 publications
(591 citation statements)
references
References 97 publications
58
497
1
13
Order By: Relevance
“…According to current network models of ADHD, DMN and TPNs are, respectively, specialized for introspective vs. extrospective orientations of attention (19,20). Individuals with ADHD are proposed to exhibit insufficient regulatory control over DMN (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to current network models of ADHD, DMN and TPNs are, respectively, specialized for introspective vs. extrospective orientations of attention (19,20). Individuals with ADHD are proposed to exhibit insufficient regulatory control over DMN (40).…”
Section: Discussionmentioning
confidence: 99%
“…According to current theoretical models (19,20), inattention in ADHD involves altered competitive balance between (i) default network, an ICN implicated in internally directed mentation (21, 22); and (ii) several task-positive ICNs (TPNs), including dorsal attention network (DAN), ventral attention network (VAN), and frontoparietal network (FPN), which are involved in cognitively demanding externally focused processing. Consistent with these models, previous resting state fMRI studies in ADHD have reliably found abnormalities in functional connections within DMN (23,24) and in its interconnections with TPNs (25-27).…”
mentioning
confidence: 99%
“…However, these network abnormalities are not the only factors responsible for ADHD; instead, they are only part of the pathophysiology of ADHD [36]. In order to fully characterize the disorder, a next step for neuroscience researchers in this area is to expand their investigation beyond dysfunction of prefrontal-striatal circuitry, to consider the large-scale neural systems involved in ADHD including frontoparietal, dorsal attentional, motor, visual, and default networks [33,37].…”
Section: Clinical Studies and Implications Of The Translational Prevementioning
confidence: 99%
“…These circuits are known as the cognitive-attentional network, underlying important higher brain functions such as executive control, cognition, selective and divided attention, vigilance and working memory [38,39] . Restingstate [40] and cognitive [41,42] neuroimaging findings have consistently shown hypoactivity in these circuits in ADHD patients.…”
Section: Discusstion U S I N G T H E R E H O M E T H O D W E F O Umentioning
confidence: 99%